Increasing the Yield and Quality of Winter Wheat Grain through the Use of Innovative Fertilizers and Agricultural Machinery - Vladimir A. Milyutkin; Vladimir A. Ovchinnikov (Инженерные технологии и системы, 2023)
Introduction. The article deals with the study of optimizing the process of using liquid nitrogen mineral fertilizers based on a carbamide-ammonia mixture, both in the serial form of CAS-32 and in the innovative CAS+S (with the addition of a mesoelement-sulfur-S), as a top dressing for winter wheat during tillering in spring. The dressing process was carried out superficially on crops with a serial rod sprayer Tuman-2 with large-drop nozzles and an innovative multi-injector unit Tuman-2M. Aim of the Article. The article aims at justifying rational technologies with the main components of the effective application of CAS on the main types of crops. Materials and Methods. In the course of the study, there were used a common methodology of field experience, OST and GOST standards for testing machines for fertilization. Liquid nitrogen mineral fertilizers CAS-32 and CAS+S produced by PJSC Kuibyshev- Azot and taken as objects of research were introduced by sprayers Tuman-2 and Tuman- 2M manufactured by the company Pegas-Agro LLC. Results. The field comparative tests of innovative technologies for the use of CAS conducted by Samara State Agrarian University showed an increase in the yield of the winter wheat variety Basis to 59.9% compared with the option of dressing crops with ammonium nitrate. In addition, the use of CAS+S increases the class of wheat in protein from class III to class I, in gluten from class III to class II. Discussion and Conclusion. In general, liquid mineral fertilizers of CAS have an advantage over ammonium nitrate, especially in dry years that is very topical in the conditions of predicted global warming. The results obtained are of great importance for the wider introduction of this innovative technology in the agro-industrial complex.